PROFESIONALISME PENYIDIK CYBERCRIME DI SUBDIT SIBER DIREKTORAT RESERSE KRIMINAL KHUSUS POLDA SULUT - JULIYANTO, EKO; KAUNANG, MARKUS; LIANDO, DAUD (JURNAL ADMINISTRASI PUBLIK, 2019)
Cybercrime is a crime that occurs in cyberspace which is different from criminal acts in general. In Indonesia, this is anew crime and requires special treatment. TheCybercrime Sub-Directorate of the North Sulawesi Regional PoliceSpecial Criminal Investigation is an agency that specializes in handling Cybercrime cases in the North Sulawesi region.The Professionalism factor is very important to be a benchmark for solving cybercrime cases in North Sulawesi handledby the cybercrime Sub Directorate of Special Criminal Investigation of North Sulawesi Regional Police. But seen fromthe settlement of cases in 2017 classified as still in the lower category. The purpose of this study was to determine thecause of the handling of cases conducted by Cybercrime Investigators in the Cybercrime Sub Directorate of SpecialCriminal Investigation Directorate of North Sulawesi Regional Police. This research uses a qualitative approach.Research informants were the Head of the Cybercrime Sub-Directorate, the Office of the Cybercrime Sub-Director, theCybercrime Sub-Director and 4 members of the Cybercrime Sub-Director, which totaled 7 people. Data collection usesinterview guidelines, while data analysis techniques use triangulation and data reduction techniques in terms of WellMotivation, Well Education, Well Trained, Well Equipment and Welfare. Based on the data analysis, it was concludedthat the handling of cases conducted by Cybercrime Investigators in the Cybercrime Sub-Directorate of the NorthSulawesi Regional Police Special Criminal Investigation Unit has not been carried out professionally becauseThe professionalism of Cybercrime Investigators in the Cyber Criminal Investigation Directorate of North SulawesiRegional Police is still lacking in terms of Well Motivation, Well Education and Well Equipment. Based on the resultsof the study, it can be recommended that the leadership of the Special Criminal Investigation Directorate can providemotivation by rewarding members who can resolve cases, the Leader can add personnel or members in the SpecialCriminal Investigation Cybercrime Sub Directorate who have an educational background related to CybercrimeLeadership can propose or propose an additional investigative budget in the Cyber Sub-Directorate.Keyword: Professionalism, Cybercrime, Investigator